Rectification properties of gold–alkanedithiol–graphene hybrid junctions: Enhancing performance through molecular engineering - Mohammad Norouzi; Ehsan Rahimi (Results in Physics)
In this study, we investigate the rectification properties of hybrid molecular junctions featuring gold and graphene nanoribbon (GNR) electrodes, with an alkanedithiol molecular wire covalently bonded to the gold electrode and the edges of the GNR electrode, aligned coplanarly with the GNR surface. By optimizing the alkanedithiol chain length and the edge configuration of the GNR electrode, we aim to enhance the rectification ratio (RR) and current–voltage (I–V) characteristics. Utilizing density functional tight-binding (DFTB) combined with the non-equilibrium Green’s function (NEGF) method, we analyze the transmission spectra and I–V properties of these hybrid junctions. Our findings highlight the significant influence of the GNR edges at the interface with alkanedithiol on rectification and transport behavior. Notably, the 1,4-butanedithiol molecular bridge between gold and armchair GNR electrodes achieves a rectification ratio exceeding three orders of magnitude, accompanied by low leakage current. Additionally, these junctions exhibit negative differential resistance (NDR) characteristics at specific bias voltages. These exceptional findings underscore the potential of optimized hybrid molecular junctions for stable, high-efficiency rectification and NDR applications.